Effect of Addition of Pure Titanium Powder on Mechanical Properties in Rotary Friction Welding - Özcan, Mehmet Erbil (My University, 2025)
Rotary friction welding, which is a type of friction welding method, which is used as an alternative to traditional welding methods and has many advantages over traditional methods, has become a very popular method in the last twenty years. In this study, shafts with and without powder reinforcement were welded on a conventional lathe with rotary friction welding, tensile tests and temperature analyses were performed and the results were examined. Holes of variable diameters were drilled into the center of the shafts obtained from aluminum 6061 material and pure titanium powder was added, then pressed and sintered. The prepared shafts were welded with rotary friction welding method in appropriate combinations, and according to the results obtained, while the adhesion properties at constant speed were worse as the amount and volume of powder increased, the maximum temperature value obtained during welding increased as the volume of powder increased.
Keywords: Aluminum; Tensile test; Friction welding; Temperature analysis